A Review of Systems Perspectives in Sustainability: How Systems Properties Convey Systems-Wide Dynamics - Dentoni, Domenico; Roglic, Marija; Williams, Amanda; Bansal, Pratima (Journal of Management, 2026)
As seven of nine planetary boundaries are breached, management scholars face an urgent challenge: how can organizations address complex social-ecological crises that transcend traditional organizational boundaries and objectives? Responding to this need, researchers have leveraged a plurality of systems perspectives, yet current approaches remain nascent and fragmented. In this paper, we review 25 years (2000–2024) of empirical sustainability management research across 17 leading journals. We identify core systems properties—interrelatedness, nestedness, non-linearity, and emergence—that collectively illuminate four critical systems-wide dynamics: equilibrium, disequilibrium, adaptation, and organized systems change. This systematic review offers scholars a unified framework for theorizing and addressing critical sustainability challenges facing organizations, society, and the planet.